Cooperation and Conflict the Nordic Way. Work, Welfare, and Institutional Change in Scandinavia - Hagelund, Anniken (De Gruyter, 2015)
The Nordic model attracts attention in a mixture of applause and disbelief. Among its merits, but also a precondition to its future survival, is its capacity to modify and adapt to changing circumstances. This book scrutinizes Nordic - in particular Norwegian - working life and welfare states from the perspective of institutional change. The analyses range from property rights, boardroom politics and wage formation to old-age pensions, care work and childcare policies. What emerges is a picture of societies characterized by ongoing, often incremental, social and political reform processes. Tripartite relations of coordination and negotiation in the labor market and beyond, give shape to power relations and political processes in particular ways. The close connections between labour market, welfare state, family and gender policies work to create institutional bundles - in an even stronger way than assumed in the Varieties of Capitalism literature.The book is written for students and scholars with an interest in Nordic societies, in corporatism and political processes, as well as readers interested in theoretical debate on varieties of capitalism and institutional change.